EFFECTS OF PEER TEACHING ON GRAMMAR LEARNING: DOES IT ENHANCE LEARNER AUTONOMY? - Dewantono, Satrio; Murtisari, Elisabet Titik (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2023)
Peer teaching has been widely applied in university settings to assist language learners. However, concerns have been raised about the potential impact on learner autonomy as this teaching method involves a more able learner tutoring a lower-level one. Despite this, little attention has been given to examining this issue. For this reason, this qualitative study investigates whether peer teaching can help foster tertiary EFL students' autonomy in isolated grammar learning, which may serve as more intensive training to improve metalinguistic knowledge and grammar competence within restricted time frames. Based on reports from 29 survey participants and 11 interviewees, the study finds that peer teaching can promote learning autonomy, with students engaging in various activities to enhance their learning during tutoring and/or the peer teaching program. Participants reported improvements in learning motivation, subject understanding, problem-solving skills, and monitoring and evaluating skills. However, some students, especially those with lower abilities, appeared to be more reliant on peer tutors in constructing their knowledge, providing self-study materials, and frequency of grammar self-study. This study provides crucial qualitative findings that shed light on the effects of peer teaching on learner autonomy, particularly for EFL teacher education students' grammar learning.